2016
DOI: 10.1101/gr.198937.115
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of megabase-scale somatic copy number variation using single-cell sequencing

Abstract: Megabase-scale copy number variants (CNVs) can have profound phenotypic consequences. Germline CNVs of this magnitude are associated with disease and experience negative selection. However, it is unknown whether organismal function requires that every cell maintain a balanced genome. It is possible that large somatic CNVs are tolerated or even positively selected. Single-cell sequencing is a useful tool for assessing somatic genomic heterogeneity, but its performance in CNV detection has not been rigorously te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
124
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(139 citation statements)
references
References 27 publications
13
124
2
Order By: Relevance
“…Studies have taken one of two approaches: high depth of sequencing per cell for single nucleotide variant detection 2,9 , or low-pass sequencing to identify copy number variants (CNVs) and aneuploidy 1,10,11 . In the latter approach, the lack of an efficient, cost-effective method to produce large numbers of single cell libraries has made it difficult to quantify the frequency of CNV-harboring cells at population scale, or to provide a robust analysis of heterogeneity in the context of cancer 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have taken one of two approaches: high depth of sequencing per cell for single nucleotide variant detection 2,9 , or low-pass sequencing to identify copy number variants (CNVs) and aneuploidy 1,10,11 . In the latter approach, the lack of an efficient, cost-effective method to produce large numbers of single cell libraries has made it difficult to quantify the frequency of CNV-harboring cells at population scale, or to provide a robust analysis of heterogeneity in the context of cancer 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The first single-cell study of neuronal CNVs analyzed 110 human frontal cortex neurons and found that 13 to 41% of the neurons contained at least one megabase-scale de novo CNV (6). Additional studies, which analyzed fewer neuronal genomes, confirmed that de novo CNVs occur in at least 10% of neurons (7, 8). CNVs can be shared by multiple neurons and inherited in a clonal manner (8).…”
Section: Present Understanding Of the Prevalence Of Somatic Mutation mentioning
confidence: 88%
“…Similarly, inversions can be identified through differences in the orientations of paired-end sequencing reads. Numerous approaches have been developed to identify CNVs from WGS (7, 8789), and most can be applied directly to identify somatic mutations. For example, recent studies using WGA in conjunction with WGS have identified megabase-scale de novo CNVs in human and mouse neurons based on differences in read-depth across genomic bins (69).…”
Section: Methods To Detect Somatic Mutationsmentioning
confidence: 99%
“…Large subchromosomal somatic CNVs can be detected in normal skin 82,83 and brain 8385 , and these studies report large proportions of skin cells and neurons, approximately 30–70%, that contain at least one somatic CNV, including a small number of shared CNVs that arose during development 85 . Furthermore, the analysis of clonal CNVs can also illuminate genes and lineages that are responsible for disease; for example, brain tissue from patients with hemimegalencephaly contains neurons with somatic copy-number gains of chromosome 1q (containing the growth-promoting gene AKT3 ) 85 .…”
Section: Retrospective Methods Of Lineage Tracingmentioning
confidence: 96%